2018
DOI: 10.31232/osf.io/uk9xw
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Negative health outcomes associated with food insecurity status in the United States of America: A systematic review of peer-reviewed studies

Abstract: Introduction: Social determinants of health, such as food security, are an important target for health providers, particularly in the care of patients from underserved populations, including the uninsured and socially marginalized. Preliminary research has shown that food insecurity status (FIS) is associated with negative health outcomes.Objective: We aim to present a concise, yet comprehensive resource that lists the health outcomes associated with FIS. This guide is meant to provide innovative health provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 129 publications
2
4
0
Order By: Relevance
“…However, at the same time, affirms the need to tackle food insecurity in order to effectively promote population health and the prevention and control of diet-sensitive NCDs in the region. 46 Similar to our systematic review, Arenas et al 5 found an adverse association between exposure to food insecurity and dyslipidemia, reported from 7 peer-reviewed manuscripts published between 2006-2015. By contrast, the review by Arenas et al 5 found that there is no consistent literature-wide association between body mass index and food insecurity-status; only 18 studies out of 37 reported a statistically significant association, which is more studies than we report in our current review.…”
Section: Comparison With Previous Studiessupporting
confidence: 77%
See 2 more Smart Citations
“…However, at the same time, affirms the need to tackle food insecurity in order to effectively promote population health and the prevention and control of diet-sensitive NCDs in the region. 46 Similar to our systematic review, Arenas et al 5 found an adverse association between exposure to food insecurity and dyslipidemia, reported from 7 peer-reviewed manuscripts published between 2006-2015. By contrast, the review by Arenas et al 5 found that there is no consistent literature-wide association between body mass index and food insecurity-status; only 18 studies out of 37 reported a statistically significant association, which is more studies than we report in our current review.…”
Section: Comparison With Previous Studiessupporting
confidence: 77%
“…46 Similar to our systematic review, Arenas et al 5 found an adverse association between exposure to food insecurity and dyslipidemia, reported from 7 peer-reviewed manuscripts published between 2006-2015. By contrast, the review by Arenas et al 5 found that there is no consistent literature-wide association between body mass index and food insecurity-status; only 18 studies out of 37 reported a statistically significant association, which is more studies than we report in our current review. These findings have implications for research, as the inconsistencies of results across studies merit careful assessment of the various methodologies used in the original studies.…”
Section: Comparison With Previous Studiessupporting
confidence: 77%
See 1 more Smart Citation
“…Our findings are also consistent with a wealth of research that links food insecurity to negative physical and mental health symptoms, such as depressive symptoms and generalized anxiety. [13][14][15]17,18,32,37,[48][49][50] Race, ethnicity, and income remain important factors in helping account for food insecurity variability in the U.S. Additionally, mental health symptoms and the uncertainty or generalized anxiety manifested as fear of COVID-19 matter, as well, highlighting how different these times are and how important it is that we are better prepared for the emotional uncertainty that can impact individual's sustained access to food. Many states are reporting large increases in demand for food among service providers feeding low-income, food insecure populations in America.…”
Section: Discussionmentioning
confidence: 99%
“…Living with food insecurity contributes to a host of poor outcomes that are not only immediate, hunger, and malnutrition, but long‐lasting, such as cardiovascular disease, diabetes, depression, anxiety, and even suicidal ideation (Abdurahman et al., 2019; Arenas et al., 2018; Gregory & Coleman‐Jensen, 2017; Hanson & Connor, 2014; Kamdar et al., 2021; Vercammen et al., 2019). For children, being food insecure is associated with depressive symptoms, reduced concentration, poor school performance, developmental delays, dysregulated behavior, more frequent illness with slower recoveries, and more emergency department visits and forgone medical care (Council on Community Pediatrics Committee on Nutrition, 2015; Hanson & Connor, 2014; Nagata et al., 2019; Thomas et al., 2019).…”
mentioning
confidence: 99%